Pengaruh Self Esteem dan Kepercayaan Terhadap Minat Beli iPhone Bekas di Aplikasi OLX pada Mahasiswa Universitas Islam Negeri Walisongo Semarang - Nur Aini Naimatu A’yun; Imeldylia Rahmah; Azizah Tri Utami; Khairani Zikrinawati; Zulfa Fahmy (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research aims to measure the Influence of Self-Esteem and Trust on the Purchase Intention of Used iPhones on the OLX Application among Students at UIN Walisongo. The study used linear regression analysis and a quantitative approach through probability sampling with a sample size of 100 respondents. Based on the analysis, it can be concluded that Self-Esteem and Consumer Trust have a simultaneous effect on the purchase intention of used iPhones on the OLX application with an F-value of 24.624 and a significance value of less than 0.001. Self-Esteem and Consumer Trust have a significant partial effect on the Purchase Intention of Used iPhones on the OLX Application among students at UIN Walisongo Semarang